Da Virtude ao Terror: o itinerário de um pensador revolucionário - Marcelo Alves (Princípios, 2008)
There is a kind of crisis of conscience within the enlightening thinking related to the French Revolution: on the one hand, it accepts, willingly, to do from the fall of the Old Regime one of its most beautiful and significant fruits, otherwise, it refuses, sometimes boresome, the violent means used for that and does not accept, or takes time to accept, the ideological affiliation with them. This “excessive” violence would exclusively be mass work, according to the enlightening elitism. The route in this article tries to explain, in the context of the French Revolution in general and in the thought and action of Saint-Just in particular, the relationship between revolutionary thought and action, so that we can identify the potential for violence present in this ideal that crosses the French revolutionary thought, synthesized by the idea of Virtue and that will lead to a policy of Terror.